SOIL VULNERABILITY ASSESSMENT USING THE HORIZONTAL AND VERTICAL SPECTRUM RATIO (HVSR) METHOD OF AMBIENT NOISE WAVES, EAST JAVA ,INDOSEIA - eka nurjanah wulandari; Moh Iqbal Tawaka; (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
The local site effect determines the risk level of an earthquake. East Java has a high level of seismicity. One of the earthquake mitigation efforts is to estimate the dynamic characteristics of grounf using microtremors. The purpose of this study was to determine the natural frequency distribution, amplification factor, and seismic vulnerability index. Seismic signals are obtained from stationary and temporal seimograph records from 100 measurement locations installed in the East Java and Madura regions. This study uses the horizontal and vertical spectrum ratio (HVSR) curve analysis method popularized by Nakamura (2000). The results of the study showed that the seismic vulnerability index varied from 0.25 to 54.2. Areas that have a high level of earthquake risk include Bangkalan, Gresik, Jombang, Lumajang, Malang, Mojokerto, Pasuruan, Ponorogo, Sampang. Sidoarjo, and Surabaya. Based on the history of destructive earthquakes, this area has experienced earthquake intensity ranging from III - IX MMI.